ANALISIS SIX SIGMA DENGAN DECISION ON BELIEF CHART PADA PRODUK HOT STRIP MILL - Alifia Hanifah Mumtaz; Mustafid Mustafid; Sudarno Sudarno (Jurnal Gaussian, 2021)
The Decision On Belief (DOB) control chart is a univariate control chart that was initially introduced as a solution to the problem of less than optimal control limits from the shewhart attribute diagram, especially the control chart C. The new scheme based on the DOB control chart is that the calculation step , can change the data which initially is not normally distributed into a normal distribution, then can diagnose quality control process errors. . defines belief or an assumption in the new observation vector  and . The aim of this research is to apply the DOB control chart to data that is not normally distributed, so that it becomes a normal distribution. The result of the DOB control chart shows that the value of . is between the BKA and BKB values, which indicates a statistically controlled process. In this study, using one specification limit, namely the upper specification limit (USL) given by the company, which is 15 percent of the average production. The capability index used is  for 3 sigma using the transformation result . Based on the sample data, the result shows that the  value is 0.40633 and the sigma level is 2.719, so it can be concluded that the Hot Strip Mill production process is still not capable and has not reached the level of three sigma.Keywords: Six Sigma, Decision On Belief, capability index, , DPMO, level sigma.